GEOMETRICAL ISOMERS OF RETINENE - Hubbard, Ruth (The Rockefeller University Press, 1953)
Five crystalline retinenes have been isolated, which have every appearance of being cis-trans isomers of one another. They are all-trans retinene; three apparently mono-cis isomers: neoretinenes a and b and isoretinene a; and isoretinene b, an apparently di-cis isomer. The absorption spectra of these substances display the relations expected of cis-trans isomers. The main absorption band is displaced 5.5 to 7 mµ toward shorter wave lengths for each presumptive cis linkage. Some of the presumptive cis isomers also display a cis peak at 255 to 260 mµ. All five substances yield an identical blue product on mixing with antimony chloride. All of them are converted by light to what appears to be an identical mixture of stereoisomers. Heat isomerizes them very slowly; only neoretinene b exhibits large changes on heating at 70°C. for 3 hours. The various isomers have been extensively interconverted by gentle procedures, and all of them have been converted to all-trans retinene. The present theory of cis-trans isomerism in carotenoids predicts the existence of four stable isomers of retinene. Instead we seem to have five—specifically three mono-cis forms where two are expected. There is no doubt that all these substances are closely related isomers of one another. The only point in question is whether they differ in part by something other than cis-trans configuration. One possibility, as yet little supported by evidence, is that isomerization between β- and α-ionone rings may be involved. If, however, as seems more likely, all these substances are geometrical isomers of one another, some modification is needed in the present theory of configurational relationships in this class of compounds.